Agriculture Based Food Producing Countries Are Less Secured in Food - Jesmin Aktar; Khan Md Shaiful Islam (Journal of Nutrition and Food Security)
Background: Food security of a nation depends upon availability and access to agricultural safe products like grain, fishing, forestry, livestock, etc. Agricultural products cover a large part of national GDP in food producing countries but need to assess food security status of those nations. This paper intended to discuss the food insecurity paradox, which is more apparent in some agriculture-based countries around the globe where increased agricultural GDP shares correspond to negative levels of both food security and per capita income and give an overview on the global trends. Methods: Data was collected from the publication of EIU Global Food Security Index and World Bank. A total number of 113 countries were considered for the data on food security index (FSI), per capita income, and percent employment in agriculture. Results: Countries with higher GDP contribution in agriculture have negative correlation with FSI and per capita income but have a positive relationship with the employment rate in agriculture. That means people involved in production of food are not getting food as much and this is the reason not to access food as they have less per capita income. On the other hand, countries with much less GDP contribution in agriculture had an insignificant relationship with per capita income and employment rate in agriculture. Conclusion: Countries producing less food have access to food due to per capita income from sources other than agriculture. So, the nations that contribute to the production of food are less secured in food, which may be due to low per capita income of many people involved in agriculture sector but they make a great contribution to global food security.